2004
DOI: 10.1177/120347540400800207
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Digital Clinical Photographs in Dermatopathology

Abstract: In certain cases the inclusion of a digital image may help a dermatopathologist. Digital imaging was found to be most helpful in evaluation of inflammatory disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Changes in skin lesions can readily be documented and monitored through serial imaging 6 . Clinical photography may also help histopathological diagnosis 7 . Approximately 85% of the dermatologists in New York City use camera and ratio of digital cameras is increasing 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Changes in skin lesions can readily be documented and monitored through serial imaging 6 . Clinical photography may also help histopathological diagnosis 7 . Approximately 85% of the dermatologists in New York City use camera and ratio of digital cameras is increasing 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Medical photography is used routinely by dermatologists for management of patients with skin diseases . Medical photography is also a valuable aid in education sessions for physicians, students and patients and is necessary for adequate scientific reporting and lectures.…”
mentioning
confidence: 99%
“…Medical photography is used routinely by dermatologists for management of patients with skin diseases. [1][2][3][4][5][6][7] Medical photography is also a valuable aid in education sessions for physicians, students and patients 8,9 and is necessary for adequate scientific reporting and lectures. The widespread use of digital photography resulting from the ready availability of small digital cameras and smartphones has turned medical photography into an everyday operation that is quick and easy to perform for anyone involved in the management of patients.…”
mentioning
confidence: 99%
“…Several reports in the literature show the importance of clinical photography for clinicopathological correlation in dermatology 10,11 . Fogelberg et al showed that including a clinical digital image in a dermatopathological examination may help to confirm the initial diagnosis and narrowing down the differential diagnosis, in particularly in inflammatory skin diseases, the category prominent in our cohort 11 . More recently, digital dermoscopy and telemedicine may further help improving diagnosis accuracy.…”
Section: Discussionmentioning
confidence: 75%